2015
DOI: 10.1134/s1063782615060214
|View full text |Cite
|
Sign up to set email alerts
|

Holes localized in nanostructures in an external magnetic field: g-factor and mixing of states

Abstract: The energy spectrum and wave functions of holes in the valence band in semiconductor nanosys tems, including quantum wells, quantum wires, and quantum dots, in an external magnetic field are theoret ically investigated. The dependence of Zeeman splitting of the hole ground state upon variation in the size quantization parameters with regard to the complex structure of the valence band and magnetic field induced mixing of hole states is traced. Analytical formulas for describing the Zeeman effect in the valence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The energy dependence of the longitudinal hole g factors has been described applying the theoretical model of Refs. [33,34], which has allowed us to estimate the QD parameters: size and composition. In particular, it is shown that with increasing emission energy, the height-to-diameter ratio of the QDs increases while the indium content in QD decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy dependence of the longitudinal hole g factors has been described applying the theoretical model of Refs. [33,34], which has allowed us to estimate the QD parameters: size and composition. In particular, it is shown that with increasing emission energy, the height-to-diameter ratio of the QDs increases while the indium content in QD decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In panel (b) the solid line shows the calculated longitudinal hole g factor using the model of Refs. [33,34]. Inset shows the corresponding calculated dependencies of the height-to-diameter ratio (solid line, left axis) and the indium content (dashed line, right axis) on the QD emission energy.…”
Section: Energy Dependencementioning
confidence: 99%
“…It is seen from Fig. 3 that LL are essentially non-equidistant and nonlinearly depend on the magnetic field that is caused by the mixed nature of the H1 and H2 subbands in the inverted-band regime due to a coupling between heavy-hole to light-particle states both at finite in-plane wave vectors k k (at B = 0) 16,17 and under the action of a magnetic field. 11 For the H1 subband, only the lowest Landau level (N = −2↓) contains pure heavy-hole states, which do not mix with the lightparticle states 11…”
Section: The Landau Level Fan Diagrammentioning
confidence: 99%
“…Some extra analysis is required to determine the signs of the g-tensor components. The sign is defined in such a way that when a magnetic field is applied along a certain axis and the state with a negative total-momentum projection onto this axis is the ground state, the g-factor is considered to be positive [31].…”
Section: A Sign Assignmentmentioning
confidence: 99%